Do unions shape political ideologies at work? - Matzat, Johannes; Schmeißer, Aiko (AWI discussion paper series, 2022)
Labor unions' largest potential for political influence likely arises from their direct connection to millions of individuals at the workplace. There they may change the political views of both unionizing workers as well as of their non-unionizing management which is arguably the most relevant out-group. In this paper, we analyze the impact of unionization on workers' and managers' campaign contributions at the workplace over the 1980-2016 period in the United States. Therefore, we combine establishment-level union election data with transaction-level campaign contributions to federal and local candidates. In stacked Difference-in-Differences models, we find that unionization results in a leftward shift of campaign contributions. Unionization increases the support for Democrats relative to Republicans not only among workers but also among managers. To test the validity of these findings, we perform Regression Discontinuity exercises which show that there are no differential trends along placebo vote share cutoffs and that the results hold when comparing increasingly close elections. Moreover, we provide evidence that our results are not driven by compositional changes of the workforce.
Keywords: Graue Literatur